Exploring the impacts of smoking, nutrition and physical activity on pulmonary functions - Uca, Merve; Taşdemir, Canatan; Sivrikaya, Kenan (Progress in Nutrition, 2022)
Study Objectives: The study aimed to explore the impacts of smoking, poor nutrition, and physical activity on pulmonary functions. Methods: We obtained the data regarding the participants’ consisted of 93 (50.5%) males and 91 (49.5%) females and smoking, nutrition, and physical activity status through focus group interviews. We recruited them to pulmonary function tests through ergospirometry twice. The results were evaluated by a specialist physician on expected and measured values of the FVC, FEV1, FEV1/FVC, PEF, and MEF25-75 measurements. We analyzed the data using independent and dependent samples t-tests and logistic regression analysis on SPSS 22. Results: According to the findings of the Kolmogorov-Smirnov test, the research data showed a normal distribution (p > 0.05). Thus, we compared the dichotomous variables using Paired Samples t-test. We performed a logistic regression analysis to explore the predictive impact of smoking, poor nutrition, and physical activity on the parameters of the pulmonary test. The findings revealed that smoking significantly predicted FVC (p = 0.008), FEV1 (p = 0.001), and MEF25-75 (p = 0.000). Yet, it was not the case for FEV1-FVC (p = 0.059) and PEF (p = 0.433). On the other hand, physical activity significantly predicted FVC (p = 0.000), FEV1 (p = 0.000), FEV1-FVC (p = 0.06, and MEF25-75 (p = 0.000). However, we could not suggest that physical activity predicts PEF (p = 0.062) significantly. Conclusion: We concluded that smoking, and had positive predictive impacts on pulmonary functions and that nutrition did not have any predictive effects on pulmonary functions.